Analisis Studi Kelayakan Bisnis pada Bank BTN Syariah Tahun 2023 - Angelica, Zahwa; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the business feasibility study of Bank BTN Syariah in 2023. The analysis includes various critical aspects affecting the bank's operations, namely legal aspects, marketing and market share, technical and technological aspects, human resource management, financial aspects, and environmental impact (AMDAL). As one of the largest Islamic banks in Indonesia, Bank BTN Syariah has made progress in applying Islamic principles across its banking products. However, amidst increasingly intense competition and ongoing regulatory changes, it is crucial for the bank to adapt to economic and technological developments. The findings show that Bank BTN Syariah holds a strong feasibility potential in terms of legal and marketing aspects, as well as having a solid technological infrastructure to support its operations. On the other hand, challenges for the bank lie in financial stability and better risk management. The primary recommendation for the bank is to continue innovating and strengthening existing aspects while maintaining its commitment to Islamic principles to support sustainable growth and make a positive contribution to the community and the Indonesian economyt.